Continuous wavelet transform for ferroresonance phenomena in electric power systems - EKREN, NAZMİ (ELSEVIER SCI LTD, 2013)
The common characteristics of a nonlinear system are multiple equilibrium points, limit cycles, jump resonance and sub-harmonic generation. Ferroresonance is also a nonlinear electrical phenomenon, which occurs frequently in power systems including no-load saturable transformers, transmission lines and single/three phase switching. In this work, we modeled the 380 kV West Anatolian Electric Power Network of Turkey, by performing numerical simulations using MATLAB-Simulink Power System Block-set. We generated the signals that are characteristics to the ferroresonance in order to exhibit the emergence of the nonlinear phenomenon. In addition, using the continuous wavelet transform (CWT), we observed the behavior of the ferroresonance both in time and frequency domains. Using the results of the CWT and Power Spectral Density (PSD) applications, the ferroresonance is determined from the emergence of the over voltage changes and the inter-harmonics of between +/- Delta integral Wand +/- Delta integral depending on frequency resolution +/- Delta integral. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Ferroresonance; Power system modeling; Power spectra; Power transmission line; Wavelet transform